The effect of CKD fineness on the consistency and setting time of cement paste when adding it as a partial replacement of cement - Najam, Yousif A.; Abdullah, Hamed H.; ALbarazinchi, Faizah A. (Iraqi Journal of Science, 2022)
Cement kiln dust (CKD) is a waste of cement manufacture. The disposal dust becomes an environmental threat. In order to overcome this problem, researchers are carried out to find out the economical and the efficient means of utilizing it in various applications .One of these applications is adding it as partial replacement of cement. The aim of present work is investigating the effect of CKDs fineness on the consistency and setting time of cement, when utilized as a partial replacement. the CKD was grind by jet mill and classify into 7 groups according fineness (3000 , 6000 , 7000 , 8000 , 9000 , 10000 , 11000) cm2/gm then prepared blends with (5 ,10 , 15 , 20 , 25 , 30 , 35 and 40) % replacement by CKD for each fineness ,and compare between two sources of CKD ( kufa and Bazian cement plant) which different in location and manufacturing process .The results showed that increasing of fineness lead to increasing of water demand for consistency for each CKD, with different in water amount between types of CKD. Setting time(initial and final) retarded with increase fineness of CKD of kufa plant while accelerated setting time with increase fineness of CKD of Bazian plant .where the results indicated that increasing of CKD fineness lead to increasing activity of CKD compounds which affected on cement hydration according to its activity and percent's presence of each type of CKDs .